2006
DOI: 10.1186/1743-422x-3-99
|View full text |Cite
|
Sign up to set email alerts
|

The role of crude human saliva and purified salivary MUC5B and MUC7 mucins in the inhibition of Human Immunodeficiency Virus type 1 in an inhibition assay

Abstract: Background: Despite the continuous shedding of HIV infected blood into the oral cavity and the detectable presence of the AIDS virus at a high frequency, human saliva is reported to inhibit oral transmission of HIV through kissing, dental treatment, biting, and aerosolization. The purpose of this study was to purify salivary MUC5B and MUC7 mucins from crude saliva and determine their anti-HIV-1 activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 40 publications
(56 reference statements)
1
66
0
Order By: Relevance
“…Our laboratory showed that human saliva and its purified mucin from uninfected individuals inhibit HIV-1 in an in vitro assay [10], whilst mucins from HIV-positive patients did not [11]. We also showed that crude virus-free breast milk did not inhibit the virus, while purified mucin did [12].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our laboratory showed that human saliva and its purified mucin from uninfected individuals inhibit HIV-1 in an in vitro assay [10], whilst mucins from HIV-positive patients did not [11]. We also showed that crude virus-free breast milk did not inhibit the virus, while purified mucin did [12].…”
Section: Introductionmentioning
confidence: 71%
“…The idea of investigating the role of breast milk and its mucin constituents in the inhibition of HIV-1 arose after our laboratory showed that saliva and its mucins inhibited the virus in an in vitro assay [10]. …”
Section: Discussionmentioning
confidence: 99%
“…As in the case of the MUC5B and MUC7 from HIV negative individuals [4], serial tenfold dilution, (10 -1 to 10 -4 ) of the MUC5B and MUC7 mucins, starting at 0.9 mg mucin, from HIV patients of all the different CD4 counts (< 200, 200-400 and > 400) were done in triplicate and this made no difference to infectivity (data not shown).…”
Section: Resultsmentioning
confidence: 94%
“…We hypothesized and confirmed that salivary MUC5B and MUC7 [4], breast milk mucin (MUC1) [5] and cervical or pregnancy plug mucins [6] inhibited HIV-1 activity in an in vitro inhibition assay. We have also shown the inhibition of poxvirus activity by MUC1 [7].…”
Section: Introductionmentioning
confidence: 82%
“…Defects in mucin production can lead to diseases such as ulcerative colitis when mucins are underproduced or cystic fibrosis and asthma when mucins are overproduced (4)(5)(6). In addition, studies have shown that mucins can interact with microbes, such as Helicobacter pylori, Haemophilus parainfluenzae, and human immunodeficiency virus (7)(8)(9)(10). These diseases and microbial interactions highlight the necessity of mucins as one of the body's key natural defenses; however, few studies have focused specifically on the connection between MUC5B salivary mucins and oral diseases.…”
mentioning
confidence: 99%